2018
DOI: 10.1098/rsos.180867
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring morphology of cobalt–nickel layered double hydroxide via different surfactants for high-performance supercapacitor

Abstract: Tailoring the morphology of cobalt–nickel layered double hydroxide (LDH) electrode material was successfully achieved via the process of cathodic electrodeposition by adding different surfactants (hexamethylenetetramine, dodecyltrimethylammonium bromide (DTAB) or cetyltrimethylammonium bromide). The as-prepared Co0.75Ni0.25(OH)2 samples with surfactants exhibited wrinkle-like, cauliflower-like or net-like structures that corresponded to better electrochemical performances than the untreated one. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In all samples, FT‐IR spectra (Figure S3) show a broad peak with two contributions at 1110 and 1060 cm −1 corresponding to the asymmetric and symmetric stretching modes of S−O bonds of intercalated sulfate ions [16] . In addition, the characteristic stretching vibrations of interlayer water molecules and nitrate ions were found at 1630 cm −1 and 1384 cm −1 , respectively, corroborating the formation of a layered structure [17] …”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…In all samples, FT‐IR spectra (Figure S3) show a broad peak with two contributions at 1110 and 1060 cm −1 corresponding to the asymmetric and symmetric stretching modes of S−O bonds of intercalated sulfate ions [16] . In addition, the characteristic stretching vibrations of interlayer water molecules and nitrate ions were found at 1630 cm −1 and 1384 cm −1 , respectively, corroborating the formation of a layered structure [17] …”
Section: Resultsmentioning
confidence: 57%
“…The S 2p peak is a broad band centered at 168.7 eV, attributed to sulfate ions [20] . Finally, the O 1s peak presents two distinctive features; all the samples have a contribution centered at 531.5 eV corresponding to metal hydroxides and, moreover, the samples that were subjected to the thermal treatment exhibit a second intense band related to M−O−M bonds located at 529.8 eV [17] . This can be explained by the dehydration and the subsequent partial dehydroxylation reaction, preferentially yielding the oxide forms, [21] which was corroborated by the shift on the XRD patterns (Figure S5) for the thermally‐treated samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal oxides and hydroxides are the most widely used positive materials owing to their high theoretic capacitance [10,11,12,13]. Recently, it was found that metal-based mixed oxides/hydroxides (e.g., Co–Ni–Zn ternary oxide [14] and Co–Ni layered double hydroxide [15]) exhibit better capacitance performances compared to simple metal oxides and hydroxides. However, the low rate capability and poor cycling stability still hinder their practical applications in commercial supercapacitors.…”
Section: Introductionmentioning
confidence: 99%